A Systematic Review and Meta-analysis of Total Ankle Arthroplasty or Ankle Arthrodesis for Treatment of Osteoarthritis in Patients With Diabetes. Issue 3 (July 2022) - Tarricone, Arthur; Gee, Allen; Chen, Simon; De La Mata, Karla; Muser, Justin; Axman, Wayne; Krishnan, Prakash; Perake, Vinayak
Background: End-stage ankle osteoarthritis often requires one of 2 major surgical procedures: total ankle arthroplasty or ankle arthrodesis. Although the gold standard has been arthrodesis, patients with diabetes represent a unique cohort that requires additional considerations because of their decreased mobility and risk factors for cardiovascular complications. The purpose of this study is to review odds of major and minor adverse events for patients with diabetes and patients without diabetes in both total ankle arthroplasty and ankle arthrodesis. Methods: A total of 14 articles published between 2010 and 2020 were included in this review. Databases included PubMed, Scopus, MEDLINE/Embase, and Cochrane Library. Key words included ankle arthroplasty, total ankle arthroplasty, ankle arthrodesis, and diabetes. Results: The total number of procedures was 26 287, comprising 13 830 arthroplasty and 12 457 arthrodesis procedures. There was a significant association between patients with diabetes treated with arthrodesis and major adverse events (odds ratio [OR] 1.880, 95% CI 1.279, 2.762), whereas no significant association was observed between patients with diabetes treated with arthroplasty and major adverse events (OR 1.106, 95% CI 0.871, 1.404). Conclusion: This meta-analysis suggests patients with diabetes to be at significantly higher risk for major and minor adverse events after undergoing ankle arthrodesis. However, it suggests no significant differences in major adverse events between patients with diabetes and patients without diabetes having undergone total ankle arthroplasty. Level of Evidence: Level III, systematic review and meta-analysis.